Bu Shen Huo Xue Formula Provides Neuroprotection Against Spinal Cord Injury by Inhibits Oxidative Stress by Activating the Nrf2 Signaling Pathway - Luo D; Hou Y; Zhan J; Hou Y; Wang Z; Li X; Sui L; Chen S; Lin D (Dove Medical Press, 2024)
Dan Luo,1– 3,* Yonghui Hou,1– 3,* Jiheng Zhan,1,2,* Yu Hou,1– 3 Zenglu Wang,4 Xing Li,1,2 Lili Sui,5 Shudong Chen,1,2 Dingkun Lin1,2 1Research Laboratory of Spine Degenerative Disease, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China; 2Spinal Minimally Invasive Department, Guangdong Provincial Hospital of Chinese Medicine, Guangzhou, People’s Republic of China; 3Laboratory of Osteology and Traumatology of Traditional Chinese Medicine, Lingnan Medical Research Center, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China; 4ICU Critical Care Medicine Department, Guangdong Second Provincial Traditional Chinese Medicine Hospital, Guangzhou, People’s Republic of China; 5The First College of Clinical Medicine, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dingkun Lin; Shudong Chen, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, No. 111 Dade Road, Yuexiu District, Guangzhou, 510120, People’s Republic of China, Tel +86-020-81887233, Email lindingkuntcm@126.com; chenshudong_med@163.comPurpose: Spinal cord injury (SCI) is an irreversible neurological disease that can result in severe neurological dysfunction. The Bu Shen Huo Xue Formula (BSHXF) has been clinically shown to assist in the recovery of limb function in patients with SCI. However, the underlying mechanisms of BSHXF’s therapeutic effects remain unclear. This study aimed to evaluate the effects of BSHXF in a mouse model of SCI and to identify potential therapeutic targets.Methods: The composition of BSHXF was analyzed using high-performance liquid chromatography (HPLC). In vivo, SCI was induced in mice following established protocols, followed by administration of BSHXF. Motor function was assessed using the Basso-Beattie-Bresnahan (BBB) and footprint tests. Levels of superoxide dismutase (SOD) and malondialdehyde (MDA) were quantified with specific assay kits. Protein expression analysis was performed using Western blot and immunofluorescence. Additionally, reactive oxygen species (ROS) levels and apoptosis rates were evaluated with dedicated staining kits. In vitro, neurons were exposed to lipopolysaccharide (LPS) to investigate the effects of BSHXF on neuronal oxidative stress. The protective effects of BSHXF against LPS-induced neuronal injury were examined through RT-PCR, Western blot, and immunofluorescence.Results: The eight primary bioactive constituents of BSHXF were identified using HPLC. BSHXF significantly reduced tissue damage and enhanced functional recovery following SCI. Meanwhile, BSHXF treatment led to significant reductions in oxidative stress and apoptosis rates. It also reversed neuronal loss and reduced glial scarring after SCI. LPS exposure induced neuronal apoptosis and axonal degeneration; however, after intervention with BSHXF, neuronal damage was reduced, and the protective effects of BSHXF were mediated by the activation of the Nrf2 pathway.Conclusion: BSHXF decreased tissue damage and enhanced functional recovery after SCI by protecting neurons against oxidative stress and apoptosis. The effects of BSHXF on SCI may be related to the activation of the Nrf2 pathway.Keywords: Bu Shen Huo Xue formula, BSHXF, spinal cord injury, SCI, oxidative stress, neuroprotection, Nrf2 signaling pathway